جماعات المصالح الاقتصادية الدولية كإحدى المظاهر الجماعية لاستخدام سياسة القوة في العلاقات الدولية (Latakia University Journal - Economic and Legal Sciences Series, 2019)
إن ظاهرة استخدام القوة في العلاقات الدولية أخذت تظهر بعد الحرب العالمية الثانية وخاصة في فترة الحرب الباردة و أدت إلى تشكل المنظمات الجماعية المختلفة بهدف تنظيم ظاهرة القوة وإن مجالات تنظيم هذه الظاهرة قد تنوعت فظهر العديد من المنظمات العسكرية والسياسية والاقتصادية. إن ظهور جماعات المصالح الاقتصادية الدولية كان هدفه الأساسي تحقيق أكبر قدر ممكن من القوة اللازمة لتنفيذ الأهداف والمخططات الموضوعة للدول القائمة عليها. وهذه الجماعات، أصبحت تمارس اليوم دوراً هاماً في العلاقات الدولية وذلك ليس بصفة خفية كما كان في الماضي، بل علناً مما جعلها تزاحم الدول والمنظمات الحكومية في ميدانها الخاص ويمس نشاط جماعات المصالح الدولية عدة ميادين ( السياسة، الاقتصاد، الدين، النشاطات النقابية، وغيرها ). وفي هذا البحث قمنا بدراسة مفهوم استخدام سياسة القوة في العلاقات الدولية. مبينين كيف أصبحت جماعات المصالح الاقتصادية الدولية من أبرز الفاعلين على الساحة الدولية. The use of power in international relations began after the Second World War especially in cold war period. So, different collective organizations had been established in order to organize the power phenomenon, leading to various organizations of economic, political, and military nature. The appearance of the international economic interests groups (IEIG) had a basic aim which was to secure the maximum available power to implement plans and aims for the greatest member states. These groups have been exercising such role in international relations, openly and not secretly as was done in the past. Accordingly, they competed with governmental organizations and states in their own fields, such union activities, religion, economy, policy, and others related work. This research deals with the concept of the use of power policy in international relations and how international economic interests groups (IEIG) have to play an important role in the international arena.